(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
The pottery assemblage comprised approximately 350 sherds of various dates (Neolithic, Norse, medieval and tentatively post-medieval) indicating that the caves were a focus for sporadic activity if not continuous occupation over several successive periods in the past. A small group of well preserved bone and antler items were recovered although Antler Cave had only antler tines. Iron nails included clench nails which have a strong association with boat construction but not of any specific period. A copper-alloy pin from Wetweather Cave could have been Norse or medieval in date.